Positron annihilation characterization of free volume in micro- and macro-modified Cu0.4Co0.4Ni0.4Mn1.8O4 ceramics - Klym, H.; Ingram, A.; Shpotyuk, O.; Hadzaman, I.; Solntsev, V.; Hotra, O.; Popov, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Free volume and pore size distribution size in functional micro and macro-micro-modified Cu0.4Co0.4Ni0.4Mn1.8O4 ceramics are characterized by positron annihilation lifetime spectroscopy in comparison with Hg-porosimetry and scanning electron microscopy technique. Positron annihilation results are interpreted in terms of model implication positron trapping and ortho-positronium decaying. It is shown that free volume of positron traps are the same type for macro and micro modified Cu0.4Co0.4Ni0.4Mn1.8O4 ceramics. Classic Tao-Eldrup model in spherical approximation is used to calculation of the size of nanopores smaller than 2 nm using the ortho-positronium lifetime.